Restitution Post Bellum: Property, Inheritance, and Corrective Justice. Issue 3 (3rd June 2018) - Butt, Daniel
Abstract: When should property which was unjustly taken in wartime be returned to the victims of misappropriation, or their heirs? This article argues that Cécile Fabre's Cosmopolitan Peace understates the force of arguments favouring restitution. Rather than seeing claims for restitution made by the descendants of victims as concerned with the redress of harm, they can be understood as resting on enduring entitlements to property. This allows for an account of corrective justice which is robust across generations, and which can be justified aside from, and even sometimes in opposition to, concerns of distributive justice.